New Version of Economic Growth for Some EU Countries: Tax Discrimination-Oriented Foreign Direct Investment Hunt - ZUNGUN, DENIZ (Archives of Business Research, 2016)
Abstract This study analyzes the effects of foreign direct investments, which are claimed to be obtained through various regulations made by European Union member countries Luxemburg, Netherlands, Ireland and Belgium in the period of 2004-2013, on the economic growth of the subject countries; by comparing average values of European Union member countries. For as much as, these four subject countries achieved to attract different amounts of investments into their countries by taking advantages of gaps which take place in European Union legislation and they realized their economic growths thanks to the related investments. These four countries which are the members of European Union used the sovereign base areas of the countries and at the same time, they used taxational methods which concern European Union law, when they fulfilled their subject goals. However, today, the methods, which were used by the aforesaid countries in order to achieve the aim of increasing the economic growth, have been spotted by the European Union Commission. Despite this situation, at least the half of the countries, which are mentioned in our study, are unwilling to abandon their illegal economic growth strategies. Keywords: Foreign Direct Investment, Economic Growth, Taxation.